Penerapan Metode Struktural Analitik Sintetik (SAS) dengan Media Kartu Huruf Terhadap Kemampuan Membaca Permulaan Siswa Kelas II Sekolah Dasar - Niranty, Evania; Sofiarini, Andriana; Frima, Aren (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the completeness of the reading skills of second-grade students at SDN 1 Terawas after the implementation of the Structural Analytic Synthetic (SAS) Method using letter cards as media. The method used is a quantitative research method with an experimental research design in the one-group pre-test and post-test categories. The research population consists of all second-grade students from SDN 1 Terawas, a total of 20. Sampling was conducted using the saturation sampling technique, where the entire population is used as the sample. The data collection techniques used in this research are observation, interviews, tests, and documentation. The data obtained was analyzed using the z-test formula. Based on the calculation results, an average score of 79.6 was obtained with a completeness percentage of 85%. The research results indicate that the z-test analysis yielded Z_calculated (22.2) ≥ Z_table (1.64), thus H_a is accepted and H_o is rejected. The conclusion of this study states that the reading skills of second-grade students at SDN 1 Terawas, after the implementation of the Structural Analytic Synthetic (SAS) Method using letter cards as media, have significantly improved. Keywords: Beginning Reading, Synthetic Structural Analysis (SAS)